Influência do condicionamento ácido prévio na resistência de união de um novo sistema adesivo multi-mode aplicado às estruturas dentais - Amaral Júnior, Sinval Pereira do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objectives: The multi-mode adhesive systems are a new category recently available for commercial use, which can be applied with or without phosphoric acid etching. The aim of this study was to evaluate the bond strength of two adhesive systems (SA): Adper Single Bond 2 (SB) - conventional SA and Single Bond Universal (SBU) - multi-mode SA, when applied in different substrates: enamel (E), dentin (D) and enamel-dentin junction (AD). Materials e Methods: 54 bovine teeth were selected and in which two class II cavities (PC-II) were done (6.0mm x 4.0mm x 2.5mm). After that, the PC-II were divided into 9 groups (n=12) according to the adhesive technique and substrate to be evaluated: 1.SB/E; 2.SB/D; 3.SB/AD; 4.SBU/E; 5.SBU/D; 6.SBU/AD; 7.SBU/E-ac; 8.SBU/D-ac; 9.SBU/AD-ac. All the adhesive systems were applied according to the manufacturer's instructions in the PC-II, which were restored with Filtek Z350XT composite resin (3M ESPE), in three increments of 2.0 mm each one, light-cured for 20 seconds. After 7 days at 37oC in distilled water storage, the samples were cutted into 3 slices and the adhesive interface was reduced to a 0.8mm2 area, in hour-glass slices. The slices were submitted to microtensile bond strength test at 0.7mm/min of cross-head speed and the values calculated in MegaPascal (MPa). Results: The microtensile bond strength results (MPa) were SB/E = 16.4 (4.1); SB/D = 13.5 (4.2); SB/AD = 13.6 (5.1); SBU/E = 14.2 (1.6); SBU/D = 21.8 (9.8); SBU/AD = 18.7 (5.8); SBU/E-ac = 22.6 (3.9); SBU/D-ac = 22.1 (5.2); SBU/AD-ac = 21.8 (3.6). For the multi-mode adhesive system in self-etching technique, the enamel substrate showed lower values compared to dentin and enamel-dentin junction. For the comparison between the adhesive systems, the higher values were found for multi-mode adhesive systems...

Objetivos: Os adesivos multi-mode são uma nova categoria de sistemas adesivos inserida no mercado, que podem ser aplicados com ou sem o condicionamento ácido prévio (ac), visando simplificar a técnica de aplicação e minimizar os erros. O objetivo desta pesquisa foi avaliar in vitro a resistência de união de 2 sistemas adesivos (SA): Adper Single Bond 2 (SB) - SA convencional e Single Bond Universal (SBU) - SA multi-mode, quando aplicados nos diferentes substratos dentais: esmalte (E), dentina (D) e junção amelo-dentinária (AD). Materiais e Métodos: Foram selecionados 54 dentes bovinos e em cada dente foram confeccionados 2 preparos cavitários classe II (PC-II) padronizados (6,0mm x 4,0mm x 2,5mm). Em seguida, os PC-II foram separados aleatoriamente em 9 grupos (n=12) de acordo com a técnica adesiva utilizada e o substrato a ser analisado: 1.SB/E; 2.SB/D; 3.SB/AD; 4.SBU/E; 5.SBU/D; 6.SBU/AD; 7.SBU/E-ac; 8.SBU/D-ac; 9.SBU/AD-ac. Todos os adesivos foram aplicados conforme as instruções dos fabricantes nos PC-II, que foram restaurados com resina composta Filtek Z350XT (3M ESPE) em 3 incrementos de 2,0mm cada, fotoativando cada incremento por 20 segundos. Após 7 dias de armazenamento em água destilada à 37oC, as amostras foram seccionadas para obtenção de 3 fragmentos de cada restauração e as interfaces adesivas foram reduzidas até uma área de 0,8mm², obtendo-se espécimes em forma de ampulheta. As ampulhetas foram submetidas ao teste de microtração à velocidade de 0,7mm/min e os valores obtidos em MegaPascal (MPa). Resultados: Os valores de microtração (em MPa) obtidos de cada grupo são: SB/E = 16,4 (4,1); SB/D = 13,5 (4,2); SB/AD = 13,6 (5,1); SBU/E = 14,2 (1,6); SBU/D = 21,8 (9,8); SBU/AD = 18,7 (5,8); SBU/E-ac = 22,6 (3,9); SBU/D-ac = 22,1 (5,2); SBU/AD-ac = 21,8 (3,6). Ao avaliar...
Keywords: Esmalte dentário; Dentina; Cimentos dentários; Dental enamel